Contributions and Claims in Third Party Liability Insurances of the Entity Performing Healing Activity - Szymańska, Anna Edyta (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Legislative changes in Poland in 2011 introduced an obligation of the third party liability insurance of subjects performing healing activity. At the time of the introduction of the Act it was difficult to assess the costs associated with insurance of operating hospitals. The aim of the paper is to analyze the structure and dynamics of premiums and claims in respect of such insurance on the example of hospitals in Lodz.